[OA116] Education and training for leadership in medical physics: An EFOMP-EUTEMPE collaboration. (August 2018) - Caruana, Carmel J.; Tsapaki, Virginia; Bosmans, Hilde
Abstract : Purpose: Good leadership, managerial and strategic planning skills have become crucial in today's rapidly changing and highly competitive world. Leadership is of concern to all professions and essential for small professions such as Medical Physics. EFOMP and EUTEMPE-NET are collaborating to produce what are perhaps the most comprehensive modules for Medical Physics leadership worldwide. Methods: A SWOT analysis for the Medical Physics profession was carried out. This was followed by a comprehensive review of the literature regarding leadership in the medical and healthcare professions. Themes relevant to the profession were identified and guide the content of the modules. Results: Teaching leadership should be done in two ways: first by direct interaction with successful leaders who would share their experiences (role modeling) and secondly through formal learning. The modules provides examples of both. European leaders present their own experiences of leadership and present practical 'to do' lists for successful leadership. The formal learning is delivered using a combination of online and face-to-face phases. The online component consists of a series of sets of compulsory readings, followed by online discussions involving real-world case studies. The online phase is asynchronous so that participants would not need to take time off their clinical duties and there will not be a problem with time zones. This is followed by an onsite phase which includes discussions in which participants can discuss challenges they are facing in their own country with a panel of established leaders. Total learning time (readings, presentations, online fora etc) is 80 h. The modules can be described as 'Mini MBAs for Medical Physicists'. Conclusions: The first module 'Leadership in Medical Physics - Development of the profession and the challenges for the Medical Physics Expert in Diagnostic and Interventional Radiology' (http://eutempe-net.eu/modules/ ) has already been run successfully twice. The next run of the module starts online November 2018 whilst the onsite phase will be in Prague February 2019. Applications close September 30th 2018. Similar modules are projected for Radiation Oncology and Nuclear Medicine.